The Executorial Title of Fiduciary Guarantee in the Digitalization Era for Business Needs - Martua Eka Wijaya Tambunan; Grace Natalia Hengki Famdale; Syamsuddin; Abraham Pangihutan Sinaga (Fakultas Hukum Universitas Airlangga, 2023)
This paper aims to address the issue of executorial title in Indonesia regarding the latest regulations in fiduciary whether it is still relevant to the development of increasingly advanced information technology. The number of fiduciary disputes in the Supreme Court brings out the fact that fiduciary regulation still does not fulfill the needs of the parties involved. With regard to that matter with the issuance of the Constitutional Court’s Decision Number 18/PUU-XVII/2019, the executorial title of the fiduciary certificate seems to be dwarfed. It is important that we identify and address the issues of fiduciary guarantee which are related to the regulation of the governance system in utilizing technology to facilitate and provide protection for investors to make the atmosphere of investment in Indonesia more interesting. The methodology that will be adopted in conducting this study would be a normative legal analysis of all laws and regulations regarding fiduciary guarantees that will provide insight to society and the government, especially stakeholders who are involved in the fiduciary guarantee agreement. We hope to recommend through this paper that specific legislation be created to improve the social and legal protection of business people in order for them to be able to conduct safely and freely business activities in the investment climate of the financial industry which has the potential to boost the Indonesian economic growth.